Prevalence of pica and rumination behaviours in adults and associations with eating disorder and general psychopathology: findings form a population-based study. (9th June 2022) - Hartmann, A. S.; Zenger, M.; Glaesmer, H.; Strauß, B.; Brähler, E.; de Zwaan, M.; Hilbert, A.
Abstract: Aims: Pica and rumination disorder are known as feeding disorder diagnoses in childhood, but little is known about their occurrence in adulthood. This study aimed to assess prevalence rates of one-time and recurrent pica and rumination behaviours (PB and RB) in adults, including sociodemographic subgroups, and to examine associations with other eating disorder and general psychopathology. Methods: The representative population sample ( N = 2403) completed measures on PB and RB, symptoms of avoidant/restrictive food intake disorder (ARFID), body image and symptoms of depression and anxiety. Results: Any PB and RB were reported in 5.33 and 5.49%, respectively, while recurrent PB or RB occurred in 1.08 and 0.71%, respectively. Co-occurrence was high, with 35.29% of recurrent PB in RB, and 23.08% vice versa. Prevalence rates of recurrent PB or RB did not differ by gender, weight status, educational or migration history from those without recurrent behaviours. Adults with v . without recurrent PB and RB showed more symptoms of ARFID, general eating disorders depression and anxiety, and behavioural symptoms of eating disorders (with the exception of compensatory behaviours in recurrent PB), and less positive body image. However, there were no differences regarding age and body mass index. Conclusions: Our findings highlight the clinical significance of PB and RB in adults regarding both prevalence and associations with other psychopathological symptoms. In particular, associations with body image need to be investigated further, as in contrast to other eating disorders, body image disturbance is not yet represented in the diagnostic criteria for pica and rumination disorder. In sum, the findings highlight the need for clinical attention for these disorders and related behaviours in adults.